FITOREMEDIASI TANAH PERTANIAN TERCEMAR Cu DENGAN TANAMAN GUMITIR (Tagetes erecta L) - Siaka, I M.; Wijayanthi, I. A. G. S.; Ratnayani, O. (Jurnal Kimia (Journal of Chemistry); Vol. 18, No.1, Januari 2024, 2024)
The heavy metal Cu is a common pollutant found in agricultural soils and it contaminates the plants growing on the soils. One technique to reduce the content of heavy metal contamination in agricultural soil is through phytoremediation. The purpose of this study was to reduce the Cu content in the agricultural soil contaminated with Cu and determine the value of the bioconcentration factor (BCF) based on the Cu content in the marigold plants. The method used in this study was the remediation technique with the use of marigold plants ( Tagetes erecta L .) as a phytoremediator cultivated in Cu-contaminated soil. The results showed that the reduction in Cu content in the soil which was remediated for 20, 40, and 60 days was 8.1582, 16.4048, and 1.4583 mg/kg, while the average Cu content in marigold plants grown on the polluted soil for 20, 40 and 60 days was 11.8407, 15.7741, and 15.3062 mg/kg, respectively. Based on the results, marigold plant was classified as less effective in absorbing Cu metal which was indicated by the highest effectiveness value found when the plants grow for 40 days i.e. 13.82% (<50%). Based on the ratio of Cu metal content in the soil to its content in plant, namely 0.11-0.14%, the BCF value was <1, which means that the marigold plants were metal excluder plants, less suitable as a phytoremediator. Therefore, It is not recommended that the marigold plants do not use for phytoremediation in the soil contaminated by Cu.